P2Y Receptors in Synaptic Transmission and Plasticity: Therapeutic Potential in Cognitive Dysfunction - Segundo J. Guzman; Zoltan Gerevich (Neural Plasticity)
ATP released from neurons and astrocytes during neuronal activity or under pathophysiological circumstances is able to influence information flow in neuronal circuits by activation of ionotropic P2X and metabotropic P2Y receptors and subsequent modulation of cellular excitability, synaptic strength, and plasticity. In the present paper we review cellular and network effects of P2Y receptors in the brain. We show that P2Y receptors inhibit the release of neurotransmitters, modulate voltage- and ligand-gated ion channels, and differentially influence the induction of synaptic plasticity in the prefrontal cortex, hippocampus, and cerebellum. The findings discussed here may explain how P2Y1 receptor activation during brain injury, hypoxia, inflammation, schizophrenia, or Alzheimer’s disease leads to an impairment of cognitive processes. Hence, it is suggested that the blockade of P2Y1 receptors may have therapeutic potential against cognitive disturbances in these states.